(untitled) (Bangladesh Journal of Agricultural Research, 2016)
The experiments were carried out at the Regional Wheat Research Centre, Rajshahi of Bangladesh Agricultural Research Institute (BARI) for two consecutive years, 2009-10 and 2010-11 to evaluate the agro-economic productivity of Wheat-Rice cropping sequence as influenced by integrated plant nutrition system (IPNS) and inclusion of legume crops. The experiment comprised of four cropping sequences viz. Wheat-Mungbean- T. Aman rice, Wheat-Blackgram- T. Aman rice, Wheat-Sesbania- T. Aman rice and Wheat- Fallow- T. Aman rice; and six nutrient treatments viz. 100% recommended nutrient rates, IPNS with 3 t ha-1 poultry manure (PM), IPNS with 6 t ha-1 PM, IPNS with 5 t ha-1 cowdung (CD), IPNS with 10 t ha-1 CD and farmers practice (FP). It was carried out in a split-plot design assigning cropping sequences in the main plots and nutrient treatments in the sub-plots with three replications. For the IPNS, the 100% nutrient rates were adjusted with manure and fertilizers. Inclusion of mungbean in the Wheat-Rice cropping sequence showed higher production cost but it gave higher system productivity, gross return, gross margin, benefitcost ratio and production efficiency. This cropping sequence gave on an average 57% higher wheat equivalent yield (WEY) compared to the existing Wheat-Rice sequence followed by blackgram included cropping sequence. The IPNS based fertilizer and manure application had better yield performance, WEY, gross margin, gross return, benefit-cost ratio, production efficiency and land use efficiency as compared to 100% chemical fertilizers or FP. It is concluded that the Wheat-Mungbean-Rice cropping sequence with IPNS approach is a productive and profitable technology for crop cultivation. Bangladesh J. Agril. Res. 41(1): 17-39, March 2016